Molybdena doped titania supported TUD-C as as oxidative catalyst for styrene epoxidation - Ooi, Yee Khai (2014)
Molybdena doped titania supported on TUD-C (Mo-TiO2/TUD-C) oxidative catalyst has been synthesized and characterized. The self assembled zeolite inside the silica matrices with MFI framework has been confirmed using XRD analysis. The attainment of zeolite and MFI structures was supported by FTIR results. Crystallinity of the synthesized material decreased with increasing Si/Al ratio in the TUDC due to the formation of amorphous silica. The crystallite size of the materials was 30 nm as evidenced by TEM analysis. Among the samples prepared, Mo-TiO2/TUD-C of Si/Ti = 10 and Si/Al = 10 showed the highest catalytic activity with styrene oxide yield and selectivity of 8.42 mmol and 97%, respectively at room temperature. The increase of both Si/Ti and Si/Al ratios in Mo-TiO2/TUD-C led to poor catalytic performance due to less availability of catalytic active sites. The catalytic performance of Mo-TiO2/TUD-C was 8- fold higher than that unsupported Mo-TiO2. Results strongly suggested that TUD-C played an important role as catalyst support for the homogenous dispersion of Mo-TiO2 active sites, leading to the enhanced catalytic performance of Mo-TiO2. It has been demonstrated that Mo-TiO2/TUD-C was a good oxidative catalyst for styrene epoxidation at room temperature with high conversion and selectivity towards styrene oxide.